The implementation of zoning system in suburban schools in Tulungagung Regency, Indonesia - Ariani, Ariek Tri (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
This research aims to find out the meaning or nature; process; and the causal relationship between the school zoning system in the suburbs of Tulungagung Regency. This thesis was made using a qualitative descriptive approach with a multiple case study approach; to then associate research findings with several practical and empirical theories. These research objects are SMPN 2 Campurdarat, SMPN 1 Tanggunggunung, and SMPN 1 Besuki Tulungagung. The qualitative analysis technique used was the multiple case study, with the research instrument interviewing with school principals and acceptance of new students (PPDB) operators. This research was prepared based on several studies of the problem that the periphery school is one of the parties who benefit from implementing this zoning system compared to urban schools in Tulungagung Regency in terms of the ceiling's fulfillment. The findings of the study show that determination of the amount of ceiling in PPDB with the zoning system in schools in rural areas is following the regulations regarding the tensile strength of PPDB in Tulungagung Regency as stipulated in the Decree of the Head of the Youngest and Sports Education Office in Tulungagung Regency, Indonesia number: 188/1035/104.010/2019 concern-ing determination of schedule and capability of acceptance of new, kindergarten, elementary and middle school students in 2019/2020 academic year. The preparation of high human resources has well supported the process. The series of PPDB activities with the zoning system in rural areas in Tulungagung Regency has been carried out well by PPDB committees in each school. Evaluation of the implementation of PPDB with the zoning system in the outskirts of Tulungagung Regency has fulfilled aspects of effectiveness, efficiency, adequacy, equity, and responsiveness and accuracy; and an evaluation system has been carried out based on the principle of policy impact; i.e., comparing conditions before and after the policy is carried out.